2016
DOI: 10.1021/acs.inorgchem.5b02690
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-inflammatory—Organometallic Anticancer Compounds

Abstract: Compounds that combine metal-based drugs with covalently linked targeted organic agents have been shown, in some instances, to exhibit superior anticancer properties compared to the individual counterparts. Within this framework, we prepared a series of organometallic ruthenium(II)- and osmium(II)-p-cymene complexes modified with the nonsteroidal anti-inflammatory drugs (NSAIDs) indomethacin and diclofenac. The NSAIDs are attached to the organometallic moieties via monodentate (pyridine/phosphine) or bidentate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 110 publications
0
41
0
Order By: Relevance
“…The anticancer effects observed for cisplatin suggested that platinum and non-platinum metal-based compounds might be as valuable as organic anticancer drugs [2, 3]. Cisplatin, and a few related platinum complexes, such as carboplatin and oxaliplatin are along with the most commonly used anticancer agents [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anticancer effects observed for cisplatin suggested that platinum and non-platinum metal-based compounds might be as valuable as organic anticancer drugs [2, 3]. Cisplatin, and a few related platinum complexes, such as carboplatin and oxaliplatin are along with the most commonly used anticancer agents [4].…”
Section: Introductionmentioning
confidence: 99%
“…The extensive clinical success of platinum compounds has improved the synthesis of other platinum and non-platinum metallodrugs that might demonstrate different cytotoxic properties and characterized by a different prototype of anticancer specificities, active against cisplatin-resistant tumor cells and with an encouraging toxicological profile. Thus, in the span of three to four decades, a variety of metal compounds were investigated as potential anticancer agents based on several non-platinum metals such as ruthenium, palladium, titanium, gold and copper [210]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexes of Fe [20][21][22][23], Ru [24][25][26], Os [27,28] and Ag [29] have been found to be very active against cancer cells. Arene tricarbonylchromium group, for which the oxidation state of chromium is zero, has been attached to biological substances such as β-estradiol molecule to produce complexes that have been mainly studied for their capacity to act as a probe for the detection of biological substances by infrared spectroscopy [30].…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Ruthenium-based complexes are some of the most promising, with reported selective potency in vitro and in vivo. [17][18][19][20][21][22] McGowan et al have synthesised a range of ruthenium metal complexes for their uses as anticancer agents. [23][24][25][26] The work published on ruthenium quinaldamides showed that under inert atmosphere conditions, the filtering over NH4PF6 yielded the ruthenium quinaldamide monomers.…”
Section: Introductionmentioning
confidence: 99%